PENGARUH INVESTASI HIJAU DAN KERAGAMAN DEWAN DIREKSI TERHADAP PENGUNGKAPAN EMISI KARBON DENGAN LIPUTAN MEDIA SEBAGAI VARIABEL PEMODERASI (STUDI EMPIRIS PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2019) - Daffa Syabilla (2021)
This study aims to see the effect of Green Investment, Gender Diversity and the Nationality of Board Directors on Carbon Emission Disclosure with Media Exposure as moderation. The population in this study are companies listed on the Indonesia Stock Exchange in the 2017-2019 period. A total of 63 samples are used per year. Green Investment is measured by the PROPER award, the Gender and National Diversity of Board Directors are measured by the Blau Heterogeneity Index. Carbon Emission Disclosure is measured using a carbon emission disclosure checklist). Media Exposure is measured using the Dummy variable. The method of analysis in this study uses descriptive analysis and multiple linear regression analysis hypotheses with the help of SPSS 25. The results of this study indicate that Green Investment and the Nationality Diversitu of Board Directors have a positive and significant effect on Carbon Emission Disclosure and the relationship can be strengthened by Media Exposure. Gender Diversity of Board Directors has no effect on Carbon Emission Disclosure, and Media Exposure cannot moderate this relationship.